Categorically right? How firm-level distinctiveness affects performance across product categories - Janisch, Jonas; Vossen, Alexander (Journal of Business Venturing, 2022)
In their pursuit of “optimal distinctiveness,” firms need to simultaneously adhere to norms and stand out from the competition. Using longitudinal data from Amazon Launchpad, an online B2C marketplace for entrepreneurial products, we offer a multi-level perspective on optimal distinctiveness from a consumer goods market in which firms are active across different and heterogeneous product categories. Arguing along categorization, organizational identity, and the fit with audiences' theory of value, we challenge the assumption that firm-level distinctiveness, i.e., the distinctiveness of a firm's organizational identity and category claims, delivers equal benefits to all products it offers and showcase the decisive role of product category context. In product categories that share less overlap with other categories and thus occupy a more distinct position in the classification system, products offered by firms with high firm-level distinctiveness benefit, whereas in product categories that share frequent relations to other categories and thus occupy a non-distinct position, products do not benefit at all. This offers researchers and managers alike a new and more nuanced perspective on firm-level distinctiveness: It is not invariably efficient in addressing audiences once the “optimal” level is found, but requires careful consideration of both the firm-level appeal and the product category in which a firm seeks to operate. Firm-level distinctiveness provides firms with the means to increase the differentiation of their own products, yet this effect is most meaningful in product categories with an increasingly distinct position.